2010
DOI: 10.1007/s12032-010-9572-6
|View full text |Cite
|
Sign up to set email alerts
|

More favorable progesterone receptor phenotype of breast cancer in diabetics treated with metformin

Abstract: The coexistence of type 2 diabetes with breast cancer may result in poorer cancer-related survival due to a number of mediating factors including an alteration of tumor tissue hormonal sensitivity. Previous studies have shown that receptor status of breast tumors in diabetics may be changed; however, the mode of therapy for diabetes was usually ignored. This work presents the results of an analysis of the receptor status of breast carcinomas in 90 postmenopausal women suffering with diabetes mellitus type 2 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
(42 reference statements)
2
23
1
Order By: Relevance
“…Earlier we had published data suggesting that MF may be involved in the regulation of steroid receptor expression [26,35]. As shown in Table 2, we also found that MF mediated, although in a modest manner, differences in receptor expression.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Earlier we had published data suggesting that MF may be involved in the regulation of steroid receptor expression [26,35]. As shown in Table 2, we also found that MF mediated, although in a modest manner, differences in receptor expression.…”
Section: Discussionsupporting
confidence: 81%
“…Prior data from the first author's team (LMB) suggested that MF could alter PR levels [26,35]. Accordingly, we examined immunoblots of steroid receptors.…”
Section: Mf and Tam Effect On Steroid Receptors (Er-a And Pr)mentioning
confidence: 99%
“…A smaller study of 90 women with diabetes and breast cancer reported an increased frequency of progesterone receptor-positive breast tumours among metformin users 16 . Finally, a study from the U.S. Women's Health Initiative found that metformin users were less likely to present with invasive breast cancer; however, the authors did not explore the relationship between metformin and breast cancer stage 15 .…”
Section: Discussionmentioning
confidence: 98%
“…Whether metformin affects molecular breast cancer subtype is controversial. One study reported a reduction in hormone-sensitive tumours with metformin exposure 15 ; others reported either an increase 16,17 or no difference in hormone-positive tumours 14 . Those prior studies have been limited by small sample sizes, incomplete drug data, and inconsistent comparator groups and statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hirsh et al [41] have recently suggested metformin may selectively target cancer stem cells, and that it may act synergistically with doxorubicin, a commonly used adjuvant therapy in breast cancer. One recent report examined characteristics of breast cancer developing in 90 postmenopausal women with diabetes receiving a variety of treatments [42]. Those receiving metformin were more likely to have progesterone receptor-positive breast cancers than those receiving sulfonylureas and/or insulin, suggesting metformin may influence the type of breast cancer that develops, at least in diabetic individuals.…”
Section: Metforminmentioning
confidence: 99%